Optimizing the Growth and Production of Shallots (Allium ascalonicum L) by applying Liquid Organic Fertilizer from Kampar River Fish Waste on Ultisol Soil - Selvia - Sutriana; T. Edy Sabli; Sisca Vaulina; Ummul Muthmainnah Ulya (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Red onion is a strategic commodity because it is one of the horticultural products required for household consumption, the culinary industry, and medicinal purposes. The Kampar Regency is known for producing river fish, which the residents of Kampar and Pekanbaru consume. If this refuse is not correctly managed, it can pollute the environment. This refuse can be converted into liquid organic fertilizer (POC) due to its ability to improve soil fertility and shallot plant growth. This study aimed to determine the effect of interaction and the primary optimization of the growth and yield of shallots on ultisol soil by administering POC derived from the fish refuse of the Kampar River. The investigation was conducted in the experimental garden of the Riau Islamic University, Pekanbaru, Faculty of Agriculture. The research employed a wholly random design with two factors. The first factor consisted of four levels of concentration of river fish waste (0, 22,5, 45, 67.5, and 90 ml-1) and the second factor consisted of four levels of frequency of river fish waste (1, 2, 3, 4 times). The data were analyzed and the BNJ Advanced Test was administered at a 5% confidence level. The results indicated that the interaction and main effects were significant for plant height, number of leaves, age of tuber formation, number of tubers, wet tuber weight and dried tuber weight, with the optimal treatment consisting of 67.5 – 90 ml-1 applied three to four times.